Design of a robot arm for high intensity focused ultrasound - Mehta, Rounak Subodh (2015)
Minimally invasive and non-invasive procedures combined with the precision and control offered by robotics is bringing about a revolution in the medical world; leading to more affordable healthcare and faster recovery periods. Currently, robotic technologies are in certified use for master slave surgery. With the advances in computer technology and medical sensing, a further challenge is to use the available technology to automate a medical process. High intensity focused ultrasound (HIFU) is one such non-invasive procedure that is increasingly being used as an alternative treatment for cancer. The treatment requires a small focal region of the HIFU transducer to be swept through the volume of the tumor with the guidance of an ultrasound probe. The work embodied in this thesis involves the design and control of a robot that can maneuver over the body and position the ultrasound probe and HIFU transducer, to facilitate an automated, portable, inexpensive and non-invasive treatment for prostate cancer. This design stands out from the other robot arms used in the medical field due to it’s small size compared to other 5 degree of freedom manipulators, and high payload capacity, large workspace and range of orientations compared to robots of a similar size.